2016
DOI: 10.1111/jocn.13245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bed exercises and gum chewing on abdominal sounds, flatulence and early discharge in the early period after caesarean section

Abstract: This study provides useful information to clinician and researchers when determining practices such as postoperative standing up in early period, gum chewing and early liquid intake related to postoperative bowel functions after abdominal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…This finding was statistically highly significant and it is clinically important for maternal and infant health. 6 A previous studies made by Harma et al,11 ; Çevik and Başer; 12 Shang et al 13 showed results in accordance with the results obtained from the present study regarding shorter hospital stay postoperatively , In this study, the women who chewed gum had shorter discharge times (43.00±1.40hours) than those in the control group (47.55±1.42 hours). [11][12][13]…”
Section: Discussionsupporting
confidence: 92%
“…This finding was statistically highly significant and it is clinically important for maternal and infant health. 6 A previous studies made by Harma et al,11 ; Çevik and Başer; 12 Shang et al 13 showed results in accordance with the results obtained from the present study regarding shorter hospital stay postoperatively , In this study, the women who chewed gum had shorter discharge times (43.00±1.40hours) than those in the control group (47.55±1.42 hours). [11][12][13]…”
Section: Discussionsupporting
confidence: 92%
“…Some studies in the literature state that chewing gum increases intestinal motility after abdominal surgery, accelerates the healing process, and shortens the time to discharge from the hospital. 12 , 17 , 23 , 24 In this study, the women who chewed gum had shorter discharge times (47.17 ± 1.51 hours) than those in the control group (49.11 ± 1.62 hours). In the study of Abd-El-Maeboud et al 22 , the women in the experimental group were discharged after 40.8 hours and the women in the control group after 50.5 hours (p<0.05).…”
Section: Discussionmentioning
confidence: 51%
“…14,15,17 Studies have used different brands of chewing gum, some of which were of flavoured type. [6][7][8][9][10][11][12][13] One study has shown that xylitol ingredient in sugar free gum is associated with early recovery of bowel function and thus may be superior to non-xylitol gum. 13 Chewing gum was administered 6 hours after surgery in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…5 Few studies in the recent past have shown the efficacy of chewing gum in increasing bowel motility in caesarean section patients. [6][7][8][9][10][11][12][13] Ciardulli in a metanalysis of 17 randomised controlled trials (RCT) has states that chewing gum is a safe and inexpensive intervention for early bowel recovery in caesarean delivery patients. They also suggested administering chew gum three times a day for about 30 minutes until the first flatus is associated with early recovery of bowel motility.…”
Section: Introductionmentioning
confidence: 99%